Remote 3-Dimensional Measurement System by Theodolite Intersection - Ahmad, Anuar (Fakulti Ukur dan Harta Tanah, 1990)
This paper presents a discussion on remote di mensional measurement systems(i.e.non-contact measurement systems)which are available in the market.Most of the systems used the principle of triangulation and the method of intersection and resection. The advantages,functions and the applications of the system will also be discussed in general